2020
DOI: 10.1002/agj2.20426
|View full text |Cite
|
Sign up to set email alerts
|

Continuous grazing of mixed native warm‐season grass in the fescue belt

Abstract: Continuous, season-long (May-August) grazing is the most commonly used grazing strategy among tall fescue [Lolium arundinaceum (Schreb.) Darbysh.] belt beef (Bos taurus) producers. However, little information is available regarding the feasibility of managing native warm-season grass (NWSG) pastures in this region with continuous, season-long grazing. We compared stand sustainability, beef cattle performance, and pasture production between continuous (CONT), season-long grazing and heavy-early (HEAVY), a modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 34 publications
1
11
1
Order By: Relevance
“…CP concentration and IVTD were less than values reported for big bluestem, little bluestem, and indiangrass mixtures under clipping studies or grazing evaluations by 2-4 percentage points (Backus et al, 2017;Brazil et al, 2020;Rushing et al, 2019Rushing et al, , 2020. Differences in forage nutritive value responses among these studies and the present trial may be due to relative canopy height and stage of maturity of NWSG during the first 30 days of defoliation management.…”
Section: Forage Mass Stocking Density and Canopy Heightcontrasting
confidence: 68%
See 4 more Smart Citations
“…CP concentration and IVTD were less than values reported for big bluestem, little bluestem, and indiangrass mixtures under clipping studies or grazing evaluations by 2-4 percentage points (Backus et al, 2017;Brazil et al, 2020;Rushing et al, 2019Rushing et al, , 2020. Differences in forage nutritive value responses among these studies and the present trial may be due to relative canopy height and stage of maturity of NWSG during the first 30 days of defoliation management.…”
Section: Forage Mass Stocking Density and Canopy Heightcontrasting
confidence: 68%
“…The response of NWSGs in monoculture or mixtures to N fertilization is well reported in the literature under clipping, bioenergy, or hay production systems (Angima et al, 2009; Duran et al, 2016; Lowe et al, 2015; Popp et al, 2018; Waramit et al, 2011, 2012), with generally increased forage mass observed with seasonal N application rates of up to 168 kg N ha −1 . Forage production responses of NWSG to N fertilizer application rates under grazing are more limited (B. Anderson et al, 1988; Berg, 1995; Gillen & Berg, 1998), especially in NWSG mixed species swards (Backus et al, 2017; Brazil et al, 2020; Rushing et al, 2020). Backus et al (2017) evaluated NWSG monocultures or mixtures of big bluestem and indiangrass under continuous stocking using a similar N fertilization strategy as in the present trial with an annual spring application of 67 kg N ha −1 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations